2009
DOI: 10.1149/1.3076136
|View full text |Cite
|
Sign up to set email alerts
|

Capacity-Fading Mechanisms of LiNiO[sub 2]-Based Lithium-Ion Batteries

Abstract: The mechanism for capacity fade of lithium-ion batteries with LinormalNi0.8normalCo0.15normalAl0.05normalO2 as a positive electrode material associated with cycling at elevated temperatures was investigated by the combination of electrochemical and spectroscopic methods. The total capacity fade of the battery after charge/discharge cycle test at 80°C was found to be almost explained by the capacity fade of the positive electrode, which indicates that the degradation of the positive electrode is mainly resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 33 publications
5
84
0
2
Order By: Relevance
“…20,26,27,37 In this study, not only the disordered rocksalt structure but also the partially ordered structure was identified by STEM and EELS. An NiO-type (rock-salt structure) phase has been observed in LiNi 0.8 Co 0.2 O 2 and LiNi 0.8 Co 0.15 Al 0.05 O 2 positive electrode materials.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…20,26,27,37 In this study, not only the disordered rocksalt structure but also the partially ordered structure was identified by STEM and EELS. An NiO-type (rock-salt structure) phase has been observed in LiNi 0.8 Co 0.2 O 2 and LiNi 0.8 Co 0.15 Al 0.05 O 2 positive electrode materials.…”
Section: Resultsmentioning
confidence: 96%
“…Codoping is also possible, with the optimum composition with respect to thermal or structural stability and electrochemical reactivity in lithium cells reported to be LiNi 0.8 Co 0.15 Al 0.05 O 2 . Recently, Sasaki et al 26 and Muto et al 27 systematically studied the capacity fade of Li-ion batteries using LiNi 0.8 Co 0.15 Al 0.05 O 2 as the positive electrode. This is one of the main reasons for deterioration of lithium-ion batteries, resulting in poor cyclability and low rate capability after long-term cycling, especially at elevated temperatures.…”
mentioning
confidence: 99%
“…Internal Formation of stress-inducing microcracks at grain boundaries during long-term cycling by lattice expansion at high cut-off potentials [2], redox-irreversible second phases [3], and gradual increase in degree of cation mixing [4][5][6]. Interface interaction Solid electrolyte interface film formation, rock salt NiO-like layer that propagates from the surface into the bulk of active materials [7], Li ion consumption by lithium carbonate formation [8][9][10], and HF attack and catalyst effect of transition metals at the surface of active materials [11].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, the processes in batteries utilizing Li(Ni,Co,Al)O 2 during abuse conditions, such as overcharge cycling up to 5.0 V, are not clear in detail. Our previous research has shown that a small amount of Mg substitution in Li(Ni,Co,Al)O 2 has much impact on the electrochemical behavior.…”
mentioning
confidence: 99%